2002
DOI: 10.14310/horm.2002.1158
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of thyroid hormone levels in patients with either hyper- or hypothyroidism results in a profound change of atrial natriuretic peptide (ANP) levels

Abstract: Atrial Natriuretic Peptide (ANP) is a hormone produced by cardiac atrial myocytes. Thyroid hormones may affect its release. The aim of this study was to analyze the effect of hyper and hypothyroidism on the secretion of ANP and its relationship with the changes of the renin-angiotensinaldosterone system. Plasma ANP concentration as well as plasma renin activity (PRA) and aldosterone (ALDO) were measured in 21 patients with hyperthyroidism, 12 patients with hypothyroidism and 29 normal controls. Moreover, in 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…These changes result in preload increase and afterload reduction, leading to a significant increase in stroke volume. 23,24 A higher cardiac preload may trigger secretion of atrial natriuretic peptide (ANP); however, it is suggested that TH-induced myocardial ANP secretion in healthy subjects is not the result of a direct action on the myocardium, but rather the result of an indirect modification in cardiovascular hemodynamic leading to increased atrial stretch. Therefore, hyperthyroidism is characterized by a high cardiac output state with a remarkable increase in heart rate and cardiac preload and a reduction in peripheral vascular resistance, resulting in hyperdynamic circulation (Fig.…”
Section: Mechanisms Of Th Action On the Cardiovascular Systemmentioning
confidence: 99%
“…These changes result in preload increase and afterload reduction, leading to a significant increase in stroke volume. 23,24 A higher cardiac preload may trigger secretion of atrial natriuretic peptide (ANP); however, it is suggested that TH-induced myocardial ANP secretion in healthy subjects is not the result of a direct action on the myocardium, but rather the result of an indirect modification in cardiovascular hemodynamic leading to increased atrial stretch. Therefore, hyperthyroidism is characterized by a high cardiac output state with a remarkable increase in heart rate and cardiac preload and a reduction in peripheral vascular resistance, resulting in hyperdynamic circulation (Fig.…”
Section: Mechanisms Of Th Action On the Cardiovascular Systemmentioning
confidence: 99%
“…Furthermore, it has been shown that the production of ANP is increased by hormonal factors including thyroid hormone. Actually, hyper-or hypothyroidism is associated with altered serum ANP levels [6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…ANP is a hormone produced by cardiac atrial myocytes and thyroid hormones may affect its release. Koukoulis et al studying the effect of hyper and hypothyroidism on the secretion of ANP found that thyroid hormones affect positively ANP secretion from human cardiac myocytes [11]. Moreover, is well known that plasma ANP is elevated in several pathological conditions, including valve disease, coronary heart disease and cardiomyopathy [12].…”
Section: Discussionmentioning
confidence: 99%